Children, nature and cities rethinking the connections - Freeman, Claire; Von Heezik, Y. (Routledge, 2018)
"That children need nature for health and well-being is widely accepted, but what type of nature? Specifically, what type of nature is not only necessary but realistically available in the complex and rapidly changing worlds that children currently live in? This book examines child-nature definitions through two related concepts: the need for connecting to nature and the processes by which opportunities for such contact can be enhanced. This book analyses the available nature from a scientific perspective of habitats, species and environments, together with the role of planning, to identify how children in cities can and do connect with nature. This book challenges the notion of a universal child and childhood by recognizing children's diverse life worlds and experiences which guides them into different and complex ways of interacting with the natural world. Unfortunately not all children have the freedom to access the nature that is present in the cities where they live. This book addresses the challenge of designing biodiverse cities in which nature is readily accessible to children"...
Includes bibliographical references
Keywords: City children -- Social conditions; Nature -- Social aspects; Children and the environment; Urban ecology (Sociology); Kind; Natur; Stadt; Umweltschaden; Klimaänderung; Aufsatzsammlung